Réformer l'école pour transformer la société. L'éducation territorialisée de jeunes et adultes dans la favela de Manguinhos - Elis De Aquino (Les éditions de la Maison des sciences de l'Homme, 2020)
Schools for Youth and Adults (EJA) have emerged as a means of educating dropouts to fill the gaps in the Brazilian school system. Present throughout the country, these schools received in 2018 more than 3 million people aged 15 and over. While they are supposed to reproduce the school model by following the traditional curriculum, the way they do so varies from one school to another. For example, at the EJA located in the Manguinhos favela in Rio de Janeiro, teachers have set up a special pedagogical project whose goal goes beyond schooling. To do this, teachers use the concept of territorialized education to adapt the school to the context of the favela. This article analyses the implementation and impact of this education. It thus shows to what extent it constitutes a recomposition of the school form.